2019
DOI: 10.1111/jvh.13103
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of hepatocellular carcinoma development by magnetic resonance elastography in chronic hepatitis C patients who achieved sustained virological responses by direct‐acting antivirals

Abstract: Prediction of hepatocellular carcinoma (HCC) development after sustained virological response (SVR) is clinically important, and the usefulness of noninvasive markers for prediction HCC have been reported. The aim of this study was to compare the prediction accuracy for HCC development by noninvasive markers. A total of 346 patients with chronic hepatitis C without history of HCC who achieved SVR through direct‐acting antivirals were included. Magnetic resonance elastography (MRE) and serum fibrosis markers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Seven articles were subsequently excluded after reviewing the full text. Finally, the remaining eight eligible articles were included in this study 20–27 . Among them, Shili et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven articles were subsequently excluded after reviewing the full text. Finally, the remaining eight eligible articles were included in this study 20–27 . Among them, Shili et al .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the eight studies are summarized in Table 1. Four were prospective studies 20,24–26 and four were retrospective observational studies 21–23,27 . The total number of patients in the eight studies was 3507, and the total number of patients without prior HCC history in the eight studies was 3398.…”
Section: Resultsmentioning
confidence: 99%
“…[31] Tamaki et al also recently described liver stiffness by resonance above 3.75 kPa after 12 weeks of successful HCV response as being an independent predictive factor for HCC occurrence. [32] The present study came upon a correlation of total bilirubin values and MELD score, markers of liver function with HCC occurrence, as previously reported. [33] In addition to the risk for developing HCC over time, some of these parameters (such as bilirubin levels, AFP, platelet count and MELD score) may be associated with the presence of HCC at the time of assessing patients with cirrhosis due to hepatitis C.…”
Section: Discussionmentioning
confidence: 70%
“…One study that also identified pro-survival roles for fibrosis and myofibroblasts in a mouse model of pancreatic cancer also described a pro-survival role for vascular genes 58 . The most enriched Gene Ontology (GO) annotations in survival are indeed extracellular factors, exosomes, and metabolic pathways ( Non-invasive measurements of stiffness (MRE) and perfusion (various radiological methods) might help distinguish effects of acute stiffening from chronic stiffening which is a clear risk factor for cancer [66][67][68] .…”
Section: Discussionmentioning
confidence: 99%